Antiphagocytic activity of streptococcal M protein: selective binding of complement control protein factor H. - Horstmann, R D (1988)
Isolated complement components were used to study the regulation of the alternative complement pathway C3 convertase (EC 3.4.21.47), also called C3b,Bb, on M protein-carrying (M+) and M protein-lacking (M-) streptococci. Neither M- nor M+ streptococci directly affected the formation or dissociation of the surface-bound C3b,Bb or the inactivation of surface-bound C3b by factor I. However, the activity of the serum control protein of the alternative complement pathway, factor H, in controlling streptococcus-bound C3b and C3b,Bb was 6-8 times stronger on M+ organisms than on M- organisms. Furthermore, M+ streptococci of different serotypes and purified streptococcal M6 protein were shown to selectively bind factor H, the dissociation constants ranging from 4.5 X 10(-6) M to 6 X 10(-7) M. We conclude that the antiphagocytic activity of streptococcal M protein may be due to complement inhibition mediated by the binding of factor H. Binding of a regulatory protein appears to be a previously unrecognized route by which a pathogen is able to evade alternative pathway activation.